Philosophical Conception of Stable Verse Forms (Based on Yeghishe Charents’s Poetry Analysis) - Jrbashyan, Ashkhen (Տիգրան Մեծ)
The article is dedicated to the analysisof stable verse forms in the poetry of great Armenian poet Yeghishe Charents (1897-1937), introducing the structural opportunities for the development of the themeand the ideawith some philosophical logic.It has long been criticized that the structure of these verse forms has a clear logic, the roots of which come from ancient and medieval ritual art. Many of the stable forms of Roman poetry (sonnet, triolet, rondel, rondeau, etc.) arose from widespread national dance songs that were popular in medievalEurope, inheriting the lengthy stanza of three parts typical to them, which, in its turn, is associated with the triad often encountered in antique tragedies and odas (strophe, antistrophe and epode). Triolet, sonnet and rondeau resemble ancient superstrophe in their structure, showing the same logic of the development of the theme. Stable forms from Eastern poetry (ruba‟i, ghazal, mukhammaz, etc.) also have sound principles of structure and rhyme, which contribute to the expression of their philo-sophical content. The poetry of Yeghishe Charents, rich in stable verse forms, provides a vast opportunity to demonstrate the philosophical conception of the connection between their form and content.
Keywords: Philosophy of language; Philosophy of literature